Integrasi Berpusat pada Masyarakat: Memanfaatkan Kearifan Lokal Danau Tangkas untuk Pemberdayaan Ekonomi Pedesaan - Zevaya, Faradina; Paradillah, Fina; Muarifin, M; Padang, Evi; Wahyudin, Rifan (WIDA Publishing, 2024)
Tanjung Lanjut Village in Kecamatan Sekernan, Muaro Jambi Regency, has tourism potential, one of which is Tangkas Lake. The main attraction of this lake is Planchonia valida or, locally-known as putat tree, with its red flowers that bloom around July to August each year. The natural and cool atmosphere makes this lake a comfortable place to visit. However, despite having great tourism potential, the empowerment of the Tanjung Lanjut Village community in preserving and utilizing local wisdom is still not optimal. Several programs have been run to address this issue, including socialization of the importance of developing the tourism sector, batik making activities, and empowerment of Micro, Small and Medium Enterprises (MSMEs). Therefore, the community service activities aim to provide guidance to Tanjung Lanjut Village community in utilizing the village’s creative economic potential. Thus, it is expected that the community can improve their welfare while still preserving local wisdom as a form of developing creative business units.